Aesthetic Evolution and Control: Recent Transformations in Toyko - Allard, Momoko (UnderCurrents: Journal of Critical Environmental Studies, 2007)
Tokyo is an endless field of low-lying, non-descript buildings shaped like puzzle pieces to fit into their respective spaces and outlined by unbelievably narrow streets - some only manoeuvrable on scooter or motorbike. During the daytime, cool shades of white and mint green accent the city's ubiquitous concrete floors and walls, which at night, become camouflaged in infinite masses of neon lights in every colour. The aesthetic is one of modesty and calm chaos. It is the aggregate of millions of individuals pragmatically making use of their respective miniature territories. The aesthetic intentions of each remain in large part independent from their neighbours, and the result is an organically-evolved visual landscape.